Jung e a experiência religiosa: um processo fundamental no desenvolvimento psicológico na visão da psicologia analítica - Pedersoli, Ricardo Begiato (2018)
The main goal of this work is the deepening of Carl Gustav Jung religious thinking as a possibility of expanding knowledge in the Science of Religion field. Within the sub discipline of Psychology of Religion, Jung can be considered as an important agent, through his theoretical contributions he made possible a dialogue between psychology and religion. However, his work still needs to be studied for the interchange of assumptions, interdisciplinary, theoretical and epistemological controversies. Therefore, we propose here, search in his work the religious experience target of this work in order to reflect a specificity and the power of the same human psychological development. Jung regarding the use of the term religion does not make allusion to any religious institution. Referring only to the religious attitude inherent to every human being of any adherence to a religious creed. His symbols, cults and rituals serve as a transcendent function that results on the union of conscious and unconscious content, making the point of the jungian analytical psychology, the individualization. Our hypothesis is that there is in the jungian thinking a significant theoretical development seen the way that he has deepened in the study of religions, which would allow us to recognize the value in human psychological development through what has traditionally been called religious experience